Засоби казки як закономірності морального виховання дітей раннього та передшкільного віку - Токар, Любов; Пилявець, Тетяна (Вінниця : Твори, 2024)
The article reveals the essence of the concepts “morality”, “moral education” and “moral behavior of the older preschool children”. The problem of morality is described, as well as the views of scientists on the problem of moral qualities formation of the older preschool children. We believe that one of the effective means of influencing the child‟s emotional and moral spheres is a fairy tale that belongs to the world of the childhood. The role of a fairy tale in work with preschool children is revealed, which promotes the cognitive development of children, cultivates moral feelings and affects the child‟s personality. The peculiarities of children‟s perception and understanding of fairy tales and its significance in the formation of the ability of preschoolers to express themselves creatively have been studied. The effectiveness of the use of author‟s and fairy tales in the context of raising older preschool children has been clarified. The urgency of this problem is due to the choice of the topic of qualification work. We see that each selected and created fairy tale will awaken in preschool children a certain range of emotions (joy, experience, sadness, pity, indignation, etc.) and show the ability not only to convey these feelings, but above all, to evoke these feelings. The above theoretical provisions became the starting point of the ascertaining and formative stages of the experimental study of the process of moral qualities formation of the older preschool children by means of fairy tales. In order to clarify the real state of moral and ethical education of the older preschool children, to obtain basic data for the creation of formative experiment methods, a statement experiment was conducted.
У статті розкривається сутність понять «мораль», «моральне виховання» та «моральна поведінка дітей старшого дошкільного віку». Описано проблему моралі, а також погляди вчених на проблему формування моральних якостей дітей старшого дошкільного віку дітей. Ми вважаємо, що одним із ефективних засобів впливу на емоційну та моральну сфери дитини є казка, яка належить до світу дитинства. Розкрито роль казки в роботі з дітьми дошкільного віку, яка сприяє когнітивному розвитку дітей, виховує моральні почуття та впливає на особистість дитини. Досліджено особливості сприйняття та розуміння дітьми казок та їх значення у формуванні здатності дошкільнят до творчого самовираження. З'ясовано ефективність використання авторських та інших казок у контексті виховання дітей старшого дошкільного віку. Актуальність цієї проблеми зумовлена ​​вибором теми кваліфікаційної роботи. Ми бачимо, що кожна обрана та створена казка пробуджуватиме у дітей дошкільного віку певний спектр емоцій (радість, переживання, смуток, жаль, обурення тощо) та демонструватиме здатність не лише передавати ці почуття, але й, перш за все, викликати ці почуття. Вищезазначені теоретичні положення стали відправною точкою констатуючого та формувального етапів експериментального дослідження процесу формування моральних якостей дітей старшого дошкільного віку засобами казок. З метою з'ясування реального стану морально-етичного виховання дітей старшого дошкільного віку, отримання базових даних для створення формувальної методики експерименту було проведено констатувальний експеримент.
Keywords: moral education; moral behavior; moral consciousness; fairy tale; formation of moral and ethical education of children of senior preschool age; preschool teacher of a preschool educational institution; моральне виховання; моральна поведінка; моральна свідомість; казка; формування морально-етичного виховання дітей старшого дошкільного віку; вихователь дошкільного навчального закладу